the Analysis Ability Communication and Collaboration Student Through Learning Models Guided Inquiry Learning and Guided Discovery Learning on Material Chemical Equilibrium - Yurmaniati, Yurmaniati; Fitriza, Zonalia (Entalpi Pendidikan Kimia, 2024)
Based on interview with Teachers of SMAN 9 Padang, skills communication and collaboration not enough become attention and no ever identified _ whereas Curriculum 2013 requires teachers to develop Skills 21st century in between is communication and collaboration. one way you can bring up ability communication and collaboration student This is with implementing the Learning Model Guide Inquiry Learning (GIL) and Guide Discovery Learning (GDL). From syntax both of these models are in the implementation of the learning process student shared to in group so that student demanded more active compared to Master. Study This aim For describe is there is influence application of learning models GIL and GDL against ability communication and collaboration student class XI SMAN 9 Padang on the material equilibrium chemistry . Population study This is whole student class XI MIPA SMAN 9 Padang registered in Year Teaching 2019/2020. Sample taken with simple random sampling technique . Instrument evaluation form sheet observation and portfolio . Obtained data analyzed with use Miles and Huberman analysis. Research results with application of learning models GIL got _ percentage ability communication oral student namely 9.09% model , 90.09% proficient , and 0% developing nor beginner . Ability communication he wrote ie 90.90% very satisfactory , 9.09% satisfactory , and 0% not satisfying . ability the collaboration namely 36.36% model , 63.63% proficient , and 0% developing nor beginner . In the application of the GDL learning model , it is obtained percentage ability communication oral student namely 20% exemplary , 62.85% proficient , 17.14% developing , and 0% beginner . Ability communication he wrote ie 74.28% very satisfactory , 25.71% satisfactory , and 0% not satisfying . ability the collaboration namely 34.28% model , 65.71% proficient , and 0% developing nor beginner. Keywords : Guided Inquiry Learning, Guided Discovery Learning, communication , collaboration